Relationship of attention-deficit/hyperactivity disorder symptom severity with severity of alcohol-related problems in a sample of inpatients with alcohol use disorder - Bozkurt M (Dove Medical Press, 2016)
Muge Bozkurt,1 Cuneyt Evren,1 Gokhan Umut,1 Bilge Evren2 1Research, Treatment and Training Center for Alcohol and Substance Dependence, Bakirkoy Prof Dr Mazhar Osman Training and Research Hospital for Psychiatry, Neurology and Neurosurgery, 2Department of Psychiatry, Baltalimani State Hospital for Muskuloskeletal Disorders, Istanbul, Turkey Purpose: Attention-deficit/hyperactivity disorder (ADHD) has been shown to be related to a higher risk of developing psychiatric problems such as depressive disorders, substance use disorder, and impulsivity. Adults who have comorbid ADHD and alcohol use disorder (AUD) are at greater risk of negative outcomes. Thus, it is important to evaluate the relationship of ADHD symptoms and the severity of alcohol-related problems among patients with AUD. The aim of the present study was to evaluate the effect of ADHD symptoms on severity of alcohol-related problems, while controlling the effects of depression and impulsivity in a sample of inpatients with AUD. Patients and methods: Participants (n=190) were evaluated with the Beck Depression Inventory, the Short Form Barratt Impulsiveness Scale, the Michigan Alcohol Screening Test, and the Adult ADHD Self-Report Scale. Results: Severity of the scale scores was positively correlated with each other. Although severity of depression and impulsivity (particularly non-planning impulsivity) predicted the severity of alcohol-related problems in a linear regression model, when severity of ADHD symptoms was included in the analysis, the inattentive subscale score, in particular, predicted the severity of alcohol-related problems together with non-planning impulsivity, whereas depression was no longer a predictor. Conclusion: These findings suggest that, together with non-planning impulsivity, symptoms of ADHD (particularly inattentive factor) are an important factor that predict alcohol-related problems, while controlling the severity of depressive symptoms among inpatients with AUD. Keywords: ADHD, alcohol-related problems, alcohol use disorder, depression, impulsivity